2010
DOI: 10.1051/0004-6361/200913654
|View full text |Cite
|
Sign up to set email alerts
|

Colors and taxonomy of Centaurs and trans-Neptunian objects

Abstract: Context. The study of the surface properties of Centaurs and trans-Neptunian objects (TNOs) provides essential information about the early conditions and evolution of the outer Solar System. Due to the faintness of most of these distant and icy bodies, photometry currently constitutes the best technique to survey a statistically significant number of them. Aims. Our aim is to investigate color properties of a large sample of minor bodies of the outer Solar System, and set their taxonomic classification. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 19 publications
6
73
0
Order By: Relevance
“…9), although this is not hugely surprising, given the remarkably small uncertainties in the orbit of the object. Nevertheless, this result is reassuring, in that it tells us that the dynamical behaviour we observe for the object is truly representative, in Perna et al 2010), and the TNOs Eris (purple curve Alvarez-Candal et al 2011) and Makemake (dark blue curve Brown et al 2007). In addition, the average reflectivities of the S-and V-type asteroids are also shown (green and orange curves, respectively, Chapman et al 1993;Gaffey et al 1993).…”
Section: The Dynamics Of 2012 Dr 30supporting
confidence: 60%
See 1 more Smart Citation
“…9), although this is not hugely surprising, given the remarkably small uncertainties in the orbit of the object. Nevertheless, this result is reassuring, in that it tells us that the dynamical behaviour we observe for the object is truly representative, in Perna et al 2010), and the TNOs Eris (purple curve Alvarez-Candal et al 2011) and Makemake (dark blue curve Brown et al 2007). In addition, the average reflectivities of the S-and V-type asteroids are also shown (green and orange curves, respectively, Chapman et al 1993;Gaffey et al 1993).…”
Section: The Dynamics Of 2012 Dr 30supporting
confidence: 60%
“…A-type asteroids have similar reflectance spectra due to olivine (DeMeo et al 2009). (2005); blue triangles with errors bars correspond to the mean values of the BB, BR, RI and RR taxonomy classes of TNOs and Centaurs (Perna et al 2010), from bottom-left to top-right, respectively; the green and orange points show the median colours of the olivine bearing S-type and V-tpye asteroids, respectively (Chapman et al 1993). The big black open circle marks the solar colours (Ramírez et al 2012).…”
Section: Colours and Visual Reflectancementioning
confidence: 99%
“…We use 10 scan legs in each map, separated by 4 . The length (Perna et al 2010, and references therein). Class.…”
Section: Observationsmentioning
confidence: 99%
“…comm. ); ( j) Grundy et al (2008); (k) Perna et al (2010); (m) Peixinho et al (2004); (n) Sheppard & Jewitt (2002); (o) Belskaya et al (2003); (p) Sheppard (2007); (q) Tegler & Romanishin (1998); (r) Jewitt & Luu (1998); (s) Barucci et al (1999); (t) Tegler et al (2003); (u) Trujillo & Brown (2002); (v) Boehnhardt et al (2002); (w) Tegler (2011, priv. comm.…”
Section: Observationsmentioning
confidence: 99%
“…A taxonomic scheme based on multivariate statistics of the photometric color was proposed by Barucci et al (2005): four classes were identified indicating different composition and/or evolutional history, with increasingly red colors from the BB (blue objects) to the RR class (reddest objects). The relationship between taxonomical and dynamical classifications has been investigated in detail (Perna et al 2010) yielding somewhat inconclusive results. No direct correlation between color and dynamical parameters (in particular semi-major axis) was found.…”
Section: The Surface Composition Of Trans-neptunian Objects and Centaursmentioning
confidence: 99%